2006
DOI: 10.1002/bdm.514
|View full text |Cite
|
Sign up to set email alerts
|

No decision-maker is an Island: integrating expert advice with information acquisition

Abstract: The present research examined the social context of information acquisition. The main purpose was to examine how decision-makers' information acquisition processes changed when they were provided access to expert advice. Results indicated that all decision-makers opted to acquire advice; however, they typically did so only after completing over 75% of their own information search. Decision-makers agreed more with the advice as task complexity increased, but, in general, searched information in two stages-i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 36 publications
(67 reference statements)
2
75
0
2
Order By: Relevance
“…Also the forecasting tasks in Study 2, involving two sources of advice was clearly more complex than the tasks in the first study. Schrah et al (2006) found that people discount advice less when the task is more complex, and it may be that in such situations people are equally prepared to use expert or statistical model-based advice. Given these possibilities, future research could systematically encourage different levels of trust and/or systematically control levels of task difficulty to examine their specific effects on taking advice from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…Also the forecasting tasks in Study 2, involving two sources of advice was clearly more complex than the tasks in the first study. Schrah et al (2006) found that people discount advice less when the task is more complex, and it may be that in such situations people are equally prepared to use expert or statistical model-based advice. Given these possibilities, future research could systematically encourage different levels of trust and/or systematically control levels of task difficulty to examine their specific effects on taking advice from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…These are work tasks, assignments for school etc., all of which are influenced by the task requirements, a timetable and information quality (Byström, 2007). Moreover, in real life settings, organisational members need information, subject to task complexity and time constraints, to solve problems and complete the tasks in a satisfactory way (Schrah, Dalal, & Sniezek, 2006).…”
Section: Genuine Decision Tasksmentioning
confidence: 99%
“…They use their domain expertise while searching for information and using that information in the decision-making process. The decision makers favour searching for expert advice when task complexity exists (Schrah et al, 2006). In this regard, expert information is used to reduce the effort for information search and ensure the accuracy of the decision.…”
Section: Time Uncertainty and Task Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on Judge-Advisor Systems (see, e.g., the review by Bonaccio and Dalal, 2006) provides insights on when, why, and to which extent advice is implemented. For example, clients are more likely to follow advice when they are less knowledgeable than their advisor (e.g., Harvey and Fischer, 1997), when advice is solicited rather than provided without request (Gibbons et al, 2003), when tasks are complex (Schrah et al, 2006), when advice is accurate, and when the goals of clients and advisors are aligned (Schotter, 2003).…”
Section: Tablementioning
confidence: 99%